AB0962 Efficacy and safety of strontium ranelate in the treatment of knee osteoarthritis: A randomized, double-blind, placebo-controlled international trial. (23rd January 2014) - Cooper, C.; Chapurlat, R.; Christiansen, C.; Genant, H.; Bellamy, N.; Bensen, W.; Navarro, F.; Badurski, J.; Nasonov, E.; Chevalier, X.; Sambrook, P.; Spector, T.; et al.
Abstract : Background: Strontium ranelate (SrRan) has potential beneficial effects on cartilage degradation in OA, stimulating human cartilage matrix formation in vitro and decreasing the urinary C-terminal telopeptides of type II-collagen. SrRan has also been shown to reduce radiographic spinal OA progression and back pain in osteoporotic women with prevalent spinal OA. Objectives: We compared the efficacy and safety of SrRan with placebo in the treatment of knee osteoarthritis in a double-blind, placebo-controlled, randomised, international study (registration number: ISRCTN41323372 ) designed in accordance with the European Guidelines. Methods: Patients with primary knee osteoarthritis, Kellgren and Lawrence grade 2 or 3, joint space width (JSW) 2.5 to 5 mm, and knee pain intensity of at least 40 mm on a visual analogue scale during the month prior to selection, were randomly allocated to SrRan 1 or 2 g/day, or placebo using a centralised interactive voice response system. The primary endpoint was radiographic joint space narrowing measured as the mean change in the minimal JSW of the knee medial tibiofemoral compartment with a semiautomated centralised reading method. JSW was measured at inclusion, 12, 24, and 36 months on radiographs with a postero-anterior, weight-bearing, fixed-flexion acquisition technique. Main secondary endpoints were changes in algofunctional scores (WOMAC), changes in knee pain intensity, and proportion of radiological progressors (patients with knee JSN>0.5 mm). Safety was assessed by adverse events and haematology/biochemistry/haemostasis parameters. Results: Detailed results will be presented. The patients were included in 113 centres in 18 countries. 558 patients were assigned to SrRan 1 g/day, 566 to 2 g/day, and 559 to placebo. Mean follow-up was 29.8±10.5 months. Mean age was 62.8±7.2 years and 69% were female. Mean BMI was 30±5 kg/m 2, mean JSW was 3.50±0.83 mm, and 61% of randomised patients were Kellgren and Lawrence stage II. Conclusions: This large randomised placebo-controlled study will establish the long-term efficacyof SrRan on structure and symptoms in patients with knee osteoarthritis. Disclosure of Interest: None Declared